1988
DOI: 10.1038/bjc.1988.171
|View full text |Cite
|
Sign up to set email alerts
|

Benign ovarian teratomas: a population-based case-control study

Abstract: Summary We attempted to identify all cases of benign ovarian teratoma which occurred in two health districts in the UK during a 56 month period. The crude incidence was 8.9 cases/100,000 women. One hundred and twenty cases and 119 age-matched controls were interviewed to identify risk factors for this disease. In addition, 137 mothers completed postal questionnaires. Cases were older at leaving school, had higher social class occupations, were more often unmarried or married late, and had fewer children than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 22 publications
2
32
2
Order By: Relevance
“…No In this study, higher education was associated with an increased risk of benign ovarian teratomas. Similar evidence emerged from a previous population-based case-control study (Westhoff et al, 1988). It is difficult to interpret these findings, but diagnostic bias should be considered, since higher education or social class is a common characteristic of women with a diagnosis of benign gynecological conditions, such as seromucinous ovanan cysts (Parazzini et al, 1989), uterine fibroids (Paramni et al, 1988) or benign breast disease (Parazzini et al, 1984).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…No In this study, higher education was associated with an increased risk of benign ovarian teratomas. Similar evidence emerged from a previous population-based case-control study (Westhoff et al, 1988). It is difficult to interpret these findings, but diagnostic bias should be considered, since higher education or social class is a common characteristic of women with a diagnosis of benign gynecological conditions, such as seromucinous ovanan cysts (Parazzini et al, 1989), uterine fibroids (Paramni et al, 1988) or benign breast disease (Parazzini et al, 1984).…”
supporting
confidence: 52%
“…
(Simon et al, 1985;Westhoff et al, 1988). Epidemiological data on the issue, however, are scanty.

We report the results of a cas-control study on risk factors for benign ovarian teratomas conducted in the framework of a larger study on risk factors for benign and malignant ovarian diseases (Paramni et al, 1989;1991a

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the aetiology of germ cell tumours in women is similar to that of testicular germ cell cancer (Walker et al, 1984;Henderson et al, 1988;Walker et al, 1988;Westhoff et al, 1988;dos Santos Silva and Swerdlow, 1991). Thus, oestrogen exposure may represent an initiation role in utero, and gonadotropins may have a promoting effect in early adulthood Walker et al, 1988;dos Santos Silva and Swerdlow, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…But at times benign cystic teratoma may appear to be suspiciously malignant during initial scan due to its complex solid and cystic nature [16][17][18][19] . The malignant degeneration may be present in one to three percent of all cystic teratomas [16][17][18][19][20][21][22][23][24][25][26] . Computed Tomography (CT) scan, specifi cally diagnoses fat, calcifi cations and fat level correctly and is considered the modality of choice.…”
Section: Bodymentioning
confidence: 99%